Taxonomy of the subgenus Quedius (Raphirus) Stephens (Coleoptera: Staphylinidae: Staphylinini: Quediina) with descriptions of four new species from China - Cai, Yan-Peng; Zhou, Hong-Zhang (Zootaxa, 2015)
Four new species of the subgenus Raphirus Stephens, 1829 of the genus Quedius Stephens, 1829 (Coleoptera: Staphylinidae: Staphylinini: Quediina) are described based on specimens collected from China: Q. (Raphirus) hubeiensis sp. nov. from Hubei, Q. (Raphirus) ningxiaensis sp. nov. from Ningxia, Q. (Raphirus) spissus sp. nov. from Sichuan, and Q. (Raphirus) tenuiculus sp. nov. from Fujian. The females of Q. (Raphirus) oros Smetana, 2011 and Q. (Raphirus) shunichii Smetana, 2010 are described for the first time. Q. (Raphirus) kuiro Smetana, 1988 is recorded for the first time from China. Line drawings and color illustrations of adults and genitalia of all these species and some other ones are provided.